Anatomy and Activity Studies of Pedicularis condensata - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2017)
The genus Pedicularis comprises with 11 species, 2 of them are endemic, in Turkey. The Pedicularis species are known as sormuk, sorma, sormuk otu. Its usage is not well known in folk medicine, though the usage as food because of its nectar is recorded in East-Anatolia. According to the published studies on Pedicularis condensata Bieb. till today, it is seen that this plant takes a place in patent, taken during the hair dye studies. Additionally, various investigations on the isolation and activity of Pedicularis (Kesgerotu) species are reported in literature. According to these, the Pedicularis species contain iridoids and phenylethanoid compounds as major components. It has demonstrated that, the iridoids has antioxidant, antimicrobial, antiinflamatory, immunomodulator activities etc. and the phenylethanoid compounds show antioxidant, antibacterial, antiviral as well as antiinflamatory, hepatoprotective activities etc. In view of the isolation studies, it is possible that Pedicularis condensata shows some of these activities. The anatomical and activity studies on this species were not done. In this paper, an anatomical study and the results of activity tests of the extracts, which were obtained using various methods and different solvents, were presented. The antioxidant and antimicrobial activities, possessed by various extracts (hexane, dichloromethane, methanol and methanol macerate), which were prepared from the aerial parts (collected in Trabzon) by maceration and Soxhlet extraction, were investigated.
Keywords: Pedicularis condensata; plant anatomy; antimicrobial; antioxidant; PHENYLPROPANOID GLYCOSIDES; IRIDOID GLUCOSIDES; ANTIOXIDANT; SUPEROXIDE; AUCUBIN; ASSAY; IRAN